2011
DOI: 10.1007/s00228-011-1111-7
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on medicine use among first-generation Pakistani immigrants in Norway

Abstract: This study shows that cultural influences may affect medicine use among first-generation immigrants from Pakistan after having lived 10 years or more in Norway. Although access to drugs and basic health care services seems to be problem free, language proficiency is a considerable problem that obstructs access to information and is detrimental to the level of communication with health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…For instance, immigrants in Norway are less likely than the host population to seek somatic and/or mental primary care for both ordinary and emergency purposes, but substantial variation is observed according to country of origin, reason for immigration, and duration of residence Sandvik, Hunskaar, and Diaz 2012;Straiton, Reneflot, and Diaz 2014). Furthermore, some immigrants tend to use prescription medication incorrectly (Hakonsen, Lees, and Toverud 2014;Hakonsen and Toverud 2012). Under-utilization of health care services among immigrants has been observed in several countries, both where health care is universally available and where private insurance systems prevail (De Luca, Ponzo, and Andres 2013;Siddiqi, Zuberi, and Nguyen 2009).…”
Section: Acculturation Social Status and Social Causationmentioning
confidence: 99%
“…For instance, immigrants in Norway are less likely than the host population to seek somatic and/or mental primary care for both ordinary and emergency purposes, but substantial variation is observed according to country of origin, reason for immigration, and duration of residence Sandvik, Hunskaar, and Diaz 2012;Straiton, Reneflot, and Diaz 2014). Furthermore, some immigrants tend to use prescription medication incorrectly (Hakonsen, Lees, and Toverud 2014;Hakonsen and Toverud 2012). Under-utilization of health care services among immigrants has been observed in several countries, both where health care is universally available and where private insurance systems prevail (De Luca, Ponzo, and Andres 2013;Siddiqi, Zuberi, and Nguyen 2009).…”
Section: Acculturation Social Status and Social Causationmentioning
confidence: 99%
“…Practical training with real patients occurred during the PPE and was used by all schools. In median, 12 teaching methods were in use at each school (range [3][4][5][6][7][8][9][10][11][12][13][14]. The most commonly used textbook was "Communication Skills in Pharmacy Practice-A Practical Guide for Students and Practitioners" by Beardsley and colleagues, 35 used by four schools in five PPE courses and one CSC course.…”
Section: Resultsmentioning
confidence: 99%
“…8 Norwegian patients reported only being informed about the use of medicines in 50% of the cases. 9,10 In Iceland, pharmacists seldom gave patients evidence-based information. 11 Finnish studies on counseling found communication rates between 18% and 80%, depending on the kind of medicine dispensed, and patients reported being counseled in 46% of their visits.…”
Section: Introductionmentioning
confidence: 99%
“…If we want to improve pediatric medication safety at home, one of the most important things needed is to enhance the medication knowledge of the parents or main caregivers (Hughes & Edgerton, 2005). Culture and language barriers are thought to influence medication use and dosing accuracy among immigrants (Håkonsen & Toverud, 2012;Lo, Sharif, & Ozuah, 2006;Watt et al, 2012;Yin et al, 2010). Limited literacy proficiency and low social-economic status were the main reasons for medication errors in these populations (Chang, Chen, Chang, & Smith, 2011;Håkonsen & Toverud, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Culture and language barriers are thought to influence medication use and dosing accuracy among immigrants (Håkonsen & Toverud, 2012;Lo, Sharif, & Ozuah, 2006;Watt et al, 2012;Yin et al, 2010). Limited literacy proficiency and low social-economic status were the main reasons for medication errors in these populations (Chang, Chen, Chang, & Smith, 2011;Håkonsen & Toverud, 2012). It has been suggested that health professionals not only have to pay great attention to the communication of medical dosage information (Chang et al, 2011), but also need to put more effort into learning immigrants' beliefs about their illness and diminish the effects of unconscious bias (Suurmond, Uiters, de Bruijne, Stronks, & Essink-Bot, 2011).…”
Section: Introductionmentioning
confidence: 99%